Uma análise do fluxo de comércio intrarregional no MERCOSUL utilizando um modelo gravitacional - Cardoso, Rubiane Daniele (2011)
This paper search to analyze the effects of the formation of Mercosur Preferential Trade Agreement trade flows of member countries, using an extended gravity model that includes dummy variables for Mercosur, for UE and NAFTA (importants economic blocs), for the sectors of the economy and member country. Was used only the model of cross section data. The results show that Mercosur obtained the largest increases in trade among all regional integration schemes relevant to member countries, which highlights its importance for the members. When considering the analysis of the sectors, only agriculture had significant value, showing that the products were still predominant in this sector in the export of the Mercosur countries to all countries in the sample both in 1994, as in 2009. The analysis of dummy variables for the member countries showed that, even if the impact of the block was not uniform, the formation of MERCOSUR has had a significant effect on the pattern of exports of all its members, therefore, generally all of them experienced a significant increase in intrabloc exports during the period analyzed. With emphasis on the Paraguayan economy, that showed be strongly dependent on intraregional trade.